2017
DOI: 10.18632/oncotarget.21884
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA UCA1 indicates an unfavorable prognosis and promotes tumorigenesis via regulating AKT/GSK-3β signaling pathway in cholangiocarcinoma

Abstract: Long non-coding RNAs (lncRNAs) have been documented to play key roles in a wide range of pathophysiological processes, including cancer initiation and progression. Recently, the aberrant expression of urothelial carcinoma associated 1 (UCA1) was observed in many types of cancers. However, its clinical relevance and exact effects in cholangiocarcinoma (CCA) remains unknown. In the present study, we aimed to investigate the clinical significance of UCA1 and evaluate its prognostic value in patients with CCA. Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…Recent literatures have mainly focused on the expression pattern and the function of lncRNA UCA1 in various cancers, and the pivotally regulatory role of lncRNA UCA1 in cancer cells proliferation, invasion, migration, and apoptosis has been widely reported [13,14,17]. Besides, although the underling mechanisms of which lncRNA UCA1 functioned to malignant growth and metastasis are still a mystery, bioinformatics analyses have suggested that it might be by sponging miRNAs, and thereby quarantining the target gene of miRNAs from degradation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literatures have mainly focused on the expression pattern and the function of lncRNA UCA1 in various cancers, and the pivotally regulatory role of lncRNA UCA1 in cancer cells proliferation, invasion, migration, and apoptosis has been widely reported [13,14,17]. Besides, although the underling mechanisms of which lncRNA UCA1 functioned to malignant growth and metastasis are still a mystery, bioinformatics analyses have suggested that it might be by sponging miRNAs, and thereby quarantining the target gene of miRNAs from degradation [15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, upregulated lncRNA Sox2ot is related with lymph node invasion (P=0.0308), TNM stage (P=0.0072) and postoperative recurrence (P=0.0019) [29]. Besides, both lncRNA UCA1(urothelial carcinoma associated 1) and CCAT1 involve in CCA clinicopathological conditions [30][31][32]. Interestingly, the upregulation of lncRNA CPS1-IT1 is associated with poorer liver function [33].…”
Section: Lncrna Is Abnormally Expressed In Cca Tissuesmentioning
confidence: 99%
“…For instance, Xia, X. L. et al silenced a colorectal-cancer-related lncRNA CRNDE and observed E-cadherin was significantly increased, while N-cadherin and Vimen-tin were lost in ICC cell lines [54]. LncRNA UCA1 also can promote EMT formation [32]. When silencing UCA1, Vimentin and N-cadherin were decreased with enhanced expression of E-cadherin.…”
Section: Lncrna Promotes Emt In Cca Developmentmentioning
confidence: 99%
See 2 more Smart Citations